2021
DOI: 10.1016/j.metabol.2021.154707
|View full text |Cite
|
Sign up to set email alerts
|

Elafibranor improves diet-induced nonalcoholic steatohepatitis associated with heart failure with preserved ejection fraction in Golden Syrian hamsters

Abstract: Background: Cardiovascular disease is the leading cause of deaths in nonalcoholic steatohepatitis (NASH) patients. Mouse models, while widely used for drug development, do not fully replicate human NASH nor integrate the associated cardiac dysfunction, i.e. heart failure with preserved ejection fraction (HFpEF). To overcome these limitations, we established a nutritional hamster model developing both NASH and HFpEF. We then evaluated the effects of the dual peroxisome proliferator activated receptor alpha/delt… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
13
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 20 publications
(13 citation statements)
references
References 50 publications
0
13
0
Order By: Relevance
“…Recent clinical studies have demonstrated that NAFLD is closely associated with cardiac dysfunction or atrial fibrillation 7 , 8 , 26 . Larger rodent animals, such as hamsters and rats, with steatohepatitis accompanied by cardiomyopathy have been reported 27 , 28 ; however, there is no report regarding a mouse model. In the current study, we developed a high fat/high cholesterol/high sucrose/bile acid diet 29 .…”
Section: Discussionmentioning
confidence: 99%
“…Recent clinical studies have demonstrated that NAFLD is closely associated with cardiac dysfunction or atrial fibrillation 7 , 8 , 26 . Larger rodent animals, such as hamsters and rats, with steatohepatitis accompanied by cardiomyopathy have been reported 27 , 28 ; however, there is no report regarding a mouse model. In the current study, we developed a high fat/high cholesterol/high sucrose/bile acid diet 29 .…”
Section: Discussionmentioning
confidence: 99%
“…Liver histology (H&E and Sirius Red staining), NAFLD activity scoring and % Sirius Red labeling were performed as described previously. 62 Lung tissues were fixed in 4% PBS buffered formaldehyde for 7 days, rinsed in PBS, transferred in ethanol (70%) and then processed into paraffin-embedded tissues blocks. The subcontractor Sciempath Labo (Larçay, France) performed histological processing and analysis.…”
Section: Methodsmentioning
confidence: 99%
“…Final extraction and Mass spectrometry analysis were performed as already described. 62 SCFAs : sample preparation was adapted from protocol of Zheng and collaborators. 63 Approximatively 30 mg of fecal samples were used and suspended with 1050 µl of a solution of NaOH at 0.005 M including internal standard mix of acetate-D3, butyrate-13C2 and valerate-D9 at 61 µM and ceramic beads.…”
Section: Methodsmentioning
confidence: 99%
“…It reduced histopathologically hepatic steatosis and inflammation, and reduced fibrosis severity in both NAFLD/NASH and fibrosis mouse models [ 146 , 147 ]. It tends to reduce body weight, but not liver weight in diet-induced NAFLD/NASH rodent models [ 148 , 149 ]. In obese patients, it improves hepatic and peripheral insulin sensitivity [ 150 ].…”
Section: Non-alcoholic Fatty Liver Disease (Nafld) and Non-alcoholic Steatohepatitis (Nash)mentioning
confidence: 99%